Republic of Lithuania : 2019 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation highlights that the Lithuanian economy has continued to enjoy a strong macroeconomic and fiscal performance, but long-term challenges remain largely unaddressed. The continued strong economic performance suggests that a neutral fiscal stance would have been preferable in the year 2019. The report discusses that Lithuania needs sustained productivity gains to ensure higher living standards and convergence with Western Europe. Macroeconomic and financial stability is a prerequisite for sustained growth and has been achieved through prudent policies and labor market flexibility. Nevertheless, significant and well-identified structural challenges have yet to be addressed with ambitiously designed and decisively implemented productivity-enhancing reforms. The current expansionary cyclical environment and strong fiscal and external positions provide an ideal opportunity to address these challenges. Fintech provides big opportunities to improve financial services and produce high-skill jobs; however, it also brings challenges, particularly related to antimoney laundering. The authorities' efforts to promote fintech are already delivering results.